The effect of force saturation on the haptic perception of detail - O'Malley, M.; Goldfarb, M. (IEEE/ASME transactions on mechatronics, 2002)
This paper presents a quantitative study of the effects of maximum capable force magnitude of a haptic interface on the haptic perception of detail. Specifically, the haptic perception of detail is characterized by identification, detection, and discrimination of round and square cross-section ridges, in addition to corner detection tests. Test results indicate that performance, measured as a percent correct score in the perception experiments, improves in a nonlinear fashion as the maximum allowable level of force in the simulation increases. Further, all test subjects appeared to reach a limit in their perception capabilities at maximum-force output levels of 3-4 N, while the hardware was capable of 10 N of maximum continuous force output. These results indicate that haptic interface hardware may be able to convey sufficient perceptual information to the user with relatively low levels of force feedback. The data is compiled to aid those who wish to design a stylus-type haptic interface to meet certain requirements for the display of physical detail within a haptic simulation.